Accuracy of Preoperative Sonographic Adnexal Fixation for Prediction of Pelvic Adhesion in Gynecologic Surgery - Nuntorn Chukasemrat; Pornpun Phasipol; Maethaphan Kitporntheranunt; Somphoch Pumipichet; Kittipong Kongsomboon (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To assess the accuracy of preoperative sonographic adnexal fixation for prediction of pelvic adhesion in gynecologic surgery.Materials and Methods: This was a descriptive study of 106 gynecologic patients who were scheduled for elective abdominal surgery. Preoperative sonographic adnexal fixation was done. The accuracy of transvaginal ultrasonographic findings suspecting pelvic adhesion, including at least one side of adnexal fixation, in predicting intraoperative adnexal adhesion was calculated. Pelvic adhesion risk factors were also collected.Results: Sonographic adnexal fixation was found in 81 adnexa. Ipsilateral adnexal adhesion was found intraoperatively in 78 adnexa of this study. Overall, pelvic adhesion prediction based on ultrasonographic finding had an accuracy, sensitivity, specificity, positive and negative predictive values of 74.4, 69.2, 77.7, 66.7 and 79.7 percent respectively. History of pelvic infection and dysmenorrhea were positively correlated with pelvic adhesion (Adjusted OR, 3.50; 95%CI, 1.26-9.75; p = 0.016 and adjusted OR, 2.47; 95%CI, 1.37-4.46; p = 0.003 respectively). However, combined a history of pelvic infection and dysmenorrhea with an ultrasonographic finding showed the most correlation with pelvic adhesion.Conclusion: Preoperative adnexal fixation on transvaginal ultrasonography accurately identified patients with pelvic adhesions. Furthermore, history of pelvic infection and dysmenorrhea could increase the ability to predict pelvic adhesion.